Trivialities in metabolomics: Artifacts in extraction and analysis - Verpoorte, R.; Kim, H. K.; Choi, Y. H. (Frontiers in Molecular Biosciences, 2022)
Abstract In the past two decades metabolomics has developed to an important tool in life sciences. The major progress in the field is in fact due to continuously improving sensitivity of analytical instruments. Metabolomics has evolved over the years to enable single cell (type) analysis. In the coming period the full analysis in space and time of the micro-metabolome of cells in an organism will be feasible and help us expand our insight in the regulation of the metabolic network in cells. In this chapter, we will not deal with the details of technical aspects that could lead to the single cell analysis. Instead, we intend to go back to the basics, the trivialities that are sometimes forgotten but are crucial for any metabolomics analysis. The preanalytical phase determines the quality of the samples for the actual analysis. In the analysis solvents, stationary- and mobile phase in either extraction or chromatographic separation may influence largely the quality of the results. Therefore, setting up a protocol for a metabolomics analysis calls not only for chemical analysis but also the following questions related to pre- and post-analytical steps need to be addressed; how reliable are previously published data; what is needed for an identification of a compound; risks of artefacts due to solvents used; what extraction method, solvent, duration; what about signals in spectra or chromatograms that do not change intensity; use of green solvents. In each question our previously reported examples and some recent examples will be used to show the potential risks of artifact formation and decomposition.